2004
DOI: 10.1111/j.1365-2109.2004.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of stevia extract on the gastric mucosa of rainbow trout Oncorhynchus mykiss (Walbaum) fed dietary histamine

Abstract: Stevia extract was made from stevia stem by extraction with boiling water and fermentation. The protective effect of a Stevia extract on rainbow trout (average weight, 12 g) fed 1% of dietary histamine for 4 weeks was investigated. Administration of dietary histamine to trout did not result in a reduction in growth rate or feed consumption but caused a gastric abnormality, e.g. exfoliation of the mucosal epithelium and atrophy of mucosal lamina propria. Stevia extract protected gastric tissue from histamine‐in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
(42 reference statements)
0
16
0
1
Order By: Relevance
“…), aqueous extract of stevia, Stevia rebaudiana (Shiozaki et al . ), and ketone extracts of Cynodon dactylon , Aegle marmelos , Withania somnifera (Immanuel et al . ), and ginger, Zingiber officinale (Immanuel et al .…”
Section: Introductionmentioning
confidence: 99%
“…), aqueous extract of stevia, Stevia rebaudiana (Shiozaki et al . ), and ketone extracts of Cynodon dactylon , Aegle marmelos , Withania somnifera (Immanuel et al . ), and ginger, Zingiber officinale (Immanuel et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to vasodilatation, stevia reduced gastric mucosal damage induced by histamine in rainbow trout [21]. Stevia prevented increased contractility of the gastrointestinal smooth muscle evidenced by its antispasmodic effect in guinea pig ileum and reduced gizzard erosion in broiler chickens fed dietary histamine [21][22][23]. Moreover, stevia was suggested to be gastroprotective by regulating gastric acid secretion and preventing gastric ulcer formation in a similar manner to that of calcium channels blockers (CCB).…”
Section: Electrophysiological Vasoactive and Gastromodulatory Effecmentioning
confidence: 99%
“…Moreover, stevia was suggested to be gastroprotective by regulating gastric acid secretion and preventing gastric ulcer formation in a similar manner to that of calcium channels blockers (CCB). Studies showed that CCBs are well-established gastric acid regulators and protect the gut from ulcers [23]. Chronic cardiovascular disease leads to arterial stiffness which in turn increases pulse pressure causing a greater load on the ventricle and myocardial oxygen demand [24].…”
Section: Electrophysiological Vasoactive and Gastromodulatory Effecmentioning
confidence: 99%
“…Several studies on the effects of histamine on other fish species suggest some impact but provide little evidence of major impacts on feeding or growth. Histamine-supplemented fishmeal was reported to cause gastric lesions, abnormalities or distended stomachs in rainbow trout (Oncorhynchus mykiss; Watanabe et al 1987;Fairgrieve et al 1994;Shiozaki et al 2004). Fairgrieve et al did not find any effect of histamine (2000 mg kg )1 ) on feed intake or growth but acknowledged that the 16-week trial period may not have been sufficient for their development.…”
mentioning
confidence: 99%